STUDY PERENCANAAN PONDASI GEDUNG GUEST HOUSE 6 LANTAI DI KOTA KEDIRI - Supriyadi Supriyadi; Ahmad Ridwan; Yosef Cahyo (Faculty of Engineering, Kadiri University, 2020)
The building foundation is a lower structure that functions to carry the weight of the load to the subgrade. The foundation planning study in this study uses a bore pile type of foundation. This study uses the Meyerhoff method based on SPT data received by CV. Arya Duta. In this bore pile foundation planning, the carrying capacity of the bore pile foundation to the ground is 81.00 tons, with a depth of 26 M from the ground surface. The results of the calculation of pile drill piles get P 19.44 tons at the bottom of 26 M while the reinforcement of the pile cap is found in q 1.152 Ton / M (own weight). In the bore pile with spiral support found the results of the analysis data ((D. concrete 600 mm, Blanket 40 mm), (D reinforcement 16 mm, number of reinforcement 10), (D. stirrup 10 mm, Spacing 60 mm)). Based on the overall results of the structure, weight was found 16,771.43 Tons / M. Thus, from the analysis of equivalent lateral force loads (Fi 77.71), it was found that the construction of building structures is earthquake resistant.Pondasi merupakan struktur bawah bangunan yang berfungsi meneruskan berat suatu beban pada bangunan ke tanah dasar. Study perencanaan pondasi pada penelitian ini menggunakan pondasi tipe bore pile. Penelitian ini menggunakan metode Mayerhoff berdasarkan data SPT yang di terima oleh CV. Arya Duta. Pada perencanaan pondasi bore pile ini didapatkan kemampuan daya dukung pondasi bore pile terhadap tanah adalah sebesar 81.00 Ton, dengan kedalaman 26 M dari permukaan tanah. Hasil perhitungan tiang bor pile mendapatkan hasil P 19,44 Ton pada kedalaman 26 M. Sedangkan pada penulangan pile cap di temukan q 1,152 Ton/M (berat sendiri). Pada bore pile dengan tulangan spiral di temukan hasil data analisis ((D.beton 600 mm, Selimut 40 mm), (D tulangan 16 mm, jumlah tulangan 10), (D. sengkang 10 mm, Spasi 60 mm)). Berdasarkan hasil keseluruhan berat struktur ditemukan 16.771,43 Ton/M. Dengan demikian, dari analisis beban gaya lateral ekuivalen (Fi 77,71) didapatkan bahwa, Kontruksi struktur gedung tahan terhadap gempa.